Comparison of the Academic Performance of Students with Literate Mothers and Students with Illiterate Mothers in Kwara state, Nigeria - Fagbemi, Funmi Mowaiye - (NIU Journal of Social Sciences; Vol. 3 Núm. 2 (2017): KIU Journal of Social Sciences, Vol. 3 No. 2, September 2017, 2017)
There are important variables to academic performance. Further, mothers are very influential to what their children become. A literate and informed mother can make a difference to the academic performance of her child. This was the crux of this study; to find out if mothers educational qualification(s) is related to academic performance of subjects under study. The study was carried out in Kwara State. The one way analysis of variance (ANOVA) was the statistical tool utilized. The results revealed that mothers educational qualification was related to the performance of students.